Burnout And Psychological Well-Being Among Medical Students: A Systematic Review - M. Faizy Alam Noor Siregar; Arif Rachman; Agus Sutarman; Arfiyanti (Journal of Innovation Research and Knowledge, 2026)
Burnout is one of the most common mental health problems among medical students and has been associated with various adverse psychological outcomes. However, evidence regarding the relationship between burnout and psychological well-being remains dispersed across different indicators and study settings. This systematic review aimed to evaluate and synthesize the available evidence regarding the association between burnout and psychological well-being among medical students. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Literature searches were performed in PubMed and Google Scholar in June 2026 using keywords related to medical students, burnout, and psychological well-being. Inclusion criteria were primary observational studies published between 2020 and 2026 that assessed burnout and psychological well-being among medical students. Data were extracted and synthesized narratively based on study characteristics and key findings. Seven studies met the inclusion criteria. The findings consistently demonstrated that higher levels of burnout were associated with poorer psychological well-being among medical students. Burnout was linked to increased depression, anxiety, psychological distress, insomnia, and social dysfunction, as well as reduced quality of life. Studies also reported that students experiencing burnout were more likely to report impaired mental health and poorer psychological well-being. Across all included studies, burnout showed a negative impact on multiple dimensions of psychological well-being. Burnout is consistently associated with poorer psychological well-being among medical students. Higher burnout levels are related to increased psychological problems and reduced quality of life. These findings highlight the importance of implementing preventive strategies and mental health interventions to reduce burnout and promote psychological well-being in medical education.